2002
DOI: 10.1007/bf03190418
|View full text |Cite
|
Sign up to set email alerts
|

The effect of heat stress on the induced hepatic drug metabolizing system in rats

Abstract: The activity of the hepatic oxidative drug metabolizing system has been investigated in an experimentally-induced heat stress animal model pretreated with phenobarbitone. Female rats, unacclimatized and untrained were pretreated for 3 days with phenobarbitone as the inducing agent for the drug metabolizing systems. On the fourth day, they were restrained and exposed to an ambient temperature of 40 degrees C. One hour after acute exposures to such conditions, the activities of hepatic cytochrome P450, cytochrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Stress is a critical player in the regulation of most CYPs that could modify their activity and gene expression (Daskalopoulos et al, 2012). Decreased activity in rats (Damanhouri, 2002) and liver expression of this enzyme in mid-lactation of dairy cows due to the HS exposure (McCracken et al, 2015) were reported. Acute exposure of mouse to 40-42°C increased the expression of CYP3A in liver and promoted hepatocyte proliferation, but the exposure to 44-46°C inhibited proliferation and promoted apoptosis of hepatocytes (Li et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Stress is a critical player in the regulation of most CYPs that could modify their activity and gene expression (Daskalopoulos et al, 2012). Decreased activity in rats (Damanhouri, 2002) and liver expression of this enzyme in mid-lactation of dairy cows due to the HS exposure (McCracken et al, 2015) were reported. Acute exposure of mouse to 40-42°C increased the expression of CYP3A in liver and promoted hepatocyte proliferation, but the exposure to 44-46°C inhibited proliferation and promoted apoptosis of hepatocytes (Li et al, 2012).…”
Section: Discussionmentioning
confidence: 99%